Synthesis of nickel powder with good hydrogen evolution performance from spent Fluid Catalytic Cracking catalysts. (10th January 2023) - Cheng, Wenbo; Wu, Mingshuai; Yu, Fengshan; Tian, Maolin; Wen, Jiawei; Wang, Chunxia; Huang, Guoyong; Xu, Shengming
Abstract: The strategic metals in spent Fluid Catalytic Cracking (FCC) catalysts have attracted worldwide attention. In this work, the recovery of rare earths (lanthanum and cerium), nickel and vanadium have been achieved by acid leaching, extraction and precipitation, while the high-purity nickel powder with pretty hydrogen evolution performance has been synthesized for value-added utilization. Secondary leaching has been used for insoluble Ni power, and the total leaching rates of Ce, La, V and Ni are 96.17%, 85.86%, 99.99% and 74.62%, respectively. Rare earths have been recovered by the precipitation in primary leaching solution. The recovery rate of La is 97.11% and Ce is 99.96%. In secondary leaching solution, the impurity removal has been conducted, and the removal rate of Al and Fe is above 99.9%. Then the V and Ni are separated by solvent extraction, the extraction rate of V by N235 is 97.57%, the separation factor of Ni and V is 634.61. Finally, the high-purity NiSO4 solution(99.62%)is reduced to nickel power by the reducing agent N2 H4 ·H2 O, which was made for the hydrogen evolution reaction catalyst. When the current density is 10 mA/cm 2, the overpotential is 308 mV, and the slope of Tafel is 128 mV·dec −1 . This process provides a comprehensive recovery route of valuable metals from spent FCC catalysts for new energy industry. Graphical abstract: Image 1 Highlights: Nickel powder for hydrogen precipitation was synthesized from spent FCC catalysts. 600 °C pretreatment of spent FCC catalysts is more favorable for leaching. Valuable metals, La and Ce, were efficiently leached from spent FCC catalysts. The best experimental conditions for extraction of Ni and V by N235 were obtained. Synthesized nickel powder has good hydrogen precipitation performance under alkaline environment.